2018
DOI: 10.2478/jtes-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects of Transdisciplinary Approach to Promote Learners’ Cognitive Interest in Natural Science for Sustainable Development

Abstract: The use of transdisciplinary approach to promote learners’ interest in the acquisition of natural science at school provides new opportunities for a complex explanation of the phenomenon and improving the quality of the process of learning. The aim of the study is to explore the learners’ cognitive interest, personal participation and the approaches chosen by teachers from the perspective of transdisciplinary approach. The study characterises students’ subjective evaluations of their personal participation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This testifies the significant increase in comparison with the previous analysis in years 2005ñ2014, when only 25% of papers contained some philosophical treatise of the subject matter. However, in the present analysis only seven papers demonstrate the attempts of more or less extensive elaboration on these concepts, theories and approaches (Boj‚re, 2016;Boj‚re & Skrinda, 2016;Fedosejeva, BoËe, Romanova, Iliko, & Ivanova, 2018;Jurgena, CÁdere, & Kevia, 2018;Pipere et al, 2015;Raus, 2016;SalÓte, Drelinga, Iliko, OÔehnoviËa, & ZariÚa, 2016). Against expectations almost all of these papers contained also some empirical research, indicating that these theoretical discourses mainly served as an extensive background for empirical research.…”
Section: Research Paradigms (Jtes 2015ñ2018)mentioning
confidence: 53%
See 3 more Smart Citations
“…This testifies the significant increase in comparison with the previous analysis in years 2005ñ2014, when only 25% of papers contained some philosophical treatise of the subject matter. However, in the present analysis only seven papers demonstrate the attempts of more or less extensive elaboration on these concepts, theories and approaches (Boj‚re, 2016;Boj‚re & Skrinda, 2016;Fedosejeva, BoËe, Romanova, Iliko, & Ivanova, 2018;Jurgena, CÁdere, & Kevia, 2018;Pipere et al, 2015;Raus, 2016;SalÓte, Drelinga, Iliko, OÔehnoviËa, & ZariÚa, 2016). Against expectations almost all of these papers contained also some empirical research, indicating that these theoretical discourses mainly served as an extensive background for empirical research.…”
Section: Research Paradigms (Jtes 2015ñ2018)mentioning
confidence: 53%
“…Similarly as in the previous analysis, the majority of articles (49 or 75.4%) represented some type of empirical papers, 9.2% of all papers integrated both novel theoretical ideas and empirical research (e.g., -ipilova, Ostrovska, Jermolajeva, Aleksejeva, & OÔeh-noviËs, 2017; SalÓte et al, 2016), while 15.4% of papers were conceived as theoretical elaboration on different subjects (e.g., Álvarez-García et al, 2015;Miedema & Bertram-Troost, 2015). With regard to the methodological priorities in empirical studies, exactly like in preceding exploration (Pipere et al, 2015), qualitative research was produced most often (29.2% of papers) (e.g., Carbach & Fischer, 2017;Ulavere & Tammik, 2017), followed by quantitative studies (26.2%) (e.g., Biasutti, De Baz, & Alshawa, 2016;Eslamian, Jafari, & Neyestani, 2017) and mixed methods research (20%) (e.g., Briede, 2016;Jurgena, CÁdere, & Kevia, 2018), showing certain increase in comparison with the previous period of analysis (16.7%). Only four papers (6.2%) contained case studies (e.g., Lekunze & Strom, 2017) in comparison with 13.9% in the previous analysis.…”
Section: Research Paradigms (Jtes 2015ñ2018)mentioning
confidence: 98%
See 2 more Smart Citations
“…In [15] concluded that students have a large non-used potential to understand more deeply the nature of science and acquire the knowledge important for their future lives and work.…”
Section: Introductionmentioning
confidence: 99%